Anthony Notaras interviewed by Dimitri Rontidis in the NSW Bicentennial oral history collection - Notaras, Anthony, 1895-1991.; Rontidis, Dimitri, 1942-; N.S.W. Council on the Ageing; Oral History Association of Australia. N.S.W. Branch; NSW Bicentennial Oral History Project (1987)
Born in Kythera, Greece, Notaras speaks of his childhood memories; father coming to Australia 1900-1901; school and education; parents' backgrounds; family history; father's employment in Greece and Australia; brothers and sisters; family members who came to Australia; family home in Kythera; meals, family life; recreation; local community and environs; local crops; family values and discipline; celebrations; church and religion; religious conflict in Australia; health and illness; coming to Australia in 1908; school in Australia; life in Sydney; moving to Grafton, NSW; employment experiences, work and conditions in father's fish and fruit shop; influence of Greek cafes in Australian country towns; his lifestyle, entertainment, recreation; meeting wife when returning to Kythera; bringing her to Australia, building and running a picture theatre in Grafton; politics; World War I; treatment of immigrants during war; racism; immigrants and Aboriginals in Grafton; White Australia Policy; death of father; the Depression; his children; immigration during World War 2; Greek immigrants in Grafton; his childrens' careers.
Includes index.
Recorded by the NSW Bicentennial Oral History Project, funded by a bicentennial grant to the NSW Council on the Ageing and the Oral History Association of Australia (NSW).
Also available online
Timed summary and transcript available: 4 v. (31 p., 34 p., 30 p., 29 p.).
Keywords: Notaras, Anthony, -- 1895-1991 -- Interviews; Older people -- New South Wales -- Biography; Immigrants -- New South Wales -- Biography; New South Wales -- Social conditions -- 1901-1945.